THE EFFECT OF SERVICE QUALITY AND GOOD CORPORATE IMAGE ON THE CONSUMER SATISFACTION ON PT. PERKEBUNAN NUSANTARA V PEKANBARU (Study of By-Product PT. Perkebunan Nusantara V) - Fatimah Zahara Lubis; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Consumer satisfaction is an important part of the product marketing concept. This is supported by the quality of service and good corporate image in front of consumers which are part of the supporting factors for customer satisfaction. This study aims to determine the effect of service quality and corporate image on consumer satisfaction at PT. Nusantara V Pekanbaru Plantation. The sample of this research are 50 respondent by census method. The method used in this research is comparative causal (Ex Post Facto) which is a method to determine the relation between cause and effect with the data source is coming from primary data obtained through the interview process and distributing questionnaires which were then tested statistically through the SPSS program and secondary data using data on sales of by-products of PT. Nusantara V Pekanbaru Plantation from 2017-2020.The analytical method used in this research is descriptive analysis and quantitative. In this study, the results obtained are that Service Quality (X1) has a positive and significant effect on Consumer Satisfaction (Y), Company Image (X2) has a positive and significant impact on Consumer Decisions (Y), and Service Quality (X1) and Company Image (X2) has a positive and significant effect on Consumer Satisfaction (Y) at PT. Nusantara V Pekanbaru Plantation.Keywords: Service Quality, Corporate Image, and Consumer Satisfaction.